Asuhan Keperawatan Pada Lansia Ny.W Dengan Arthritis Gout Dalam Penerapan Implementasi Senam Ergonomis Untuk Menurunkan Nyeri : Studi Kasus - Ketut Dewi Budiari; Nova Natalia Beba; Wibawani Yunestri Mukti; Sabarulin Tarigan (Jurnal Keperawatan Muhammadiyah, 2021)
Elderly who experience pain needs to get attention with special strategies and techniques in solving problems. Implementation of ergonomic gymnastic becomes one of the right actions. The research objective was to find out and get an overview of nusing care to the elderly, Mrs.W who has arthritis gout in the implementation of ergonomic gymnastics to reduce pain in Tatura Utara Sub-District, Palu City. Descriptive case study research design, responden was 1 person, data was collected by interview, observation and physical, examination. The instrument used was an assessment format for the elderly that focused on pain problems and extremity assessment. Data analysis used was data reduction, presentation and conclusion. The results obtained from the special assessment on the elderly only focused on pain problems. The intervention conducted was the implementation of ergonomic gymnastics. The conclusion of nursing evaluation was obtained after nursing actions were carried out for 3 times which the client’s pain level was decreased. It is hoped that from the results of nursing care case study, the implementation of ergonomic gymnastics can be applied in Home Care practice for elderly.Keywords:  Nursing care, Arthritis gout, Ergonomic gymnastics, Pain, Elderly